PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN KETERAMPILAN KERJASAMA SISWA DI SEKOLAH - Laila Nursafitri (AS-SALAM, 2012)
Cooperation skills are needed in society today and in the future. Cooperation skill are also crucial to the success of social relations, especially in the society. Therefore, it is very important for students to learn these skills because these skills are not possessed child since birth, but the skills to be tought and given opportunities to practice. Cooperation skills is an important thing in life and superior democratic culture in addition to the attitude of responsibility, concern for others, open-mindedness, and creativity. In an effort to improve the skills students will require cooperation on the selection and application of learning strategies that enable students to learn directly in practicing these skills. Strategies that allow students to practice skills learned directly or in cooperation is a group of cooperative learning strategies, where the students sat with other students in a heterogeneous group with a common goal.